Bad kitty meets the baby - Bruel, Nick (Roaring Brook Press New York, 2011)
"Kitty's owners are home with a big surprise for Kitty. But what is it? Kitty, reeling in horror, thinks it's a . . . dog. The neighbor cats are convinced it's a cat. But we all know that it's really a BABY! With Nick Bruel's trademark mix of antic humor (this time involving a Kitty game show and the Kitty Olympics--which the baby wins hands down), riotous illustrations, total mayhem, and Uncle Murray Fun Facts, this may be the funniest Kitty book yet, and the one that hits closest to home. Bad Kitty Meets the Baby is the winner of the 2012 Children's Choice Book Awards for Third to Fourth Grade Book of the Year." -- Provided by Amazon.com